Effect of Poverty on Students’ Participation in the Class at Community Schools in Nepal - Thapa, Yogendra (Orchid Academia Siraha, 2022)
To analyse the effect of poverty on households towards class participation at community schools is the main objective of this study. A cross-sectional survey is conducted within two districts among five hundred thirty students adopting random sampling. Data on class participation are collected from semi structured survey questionnaires and analysed using bivariate and multivariate analysis with help of Stata 14. It is found that poverty hinders involvement in academic activities and managing learning facilities. Parents with poverty have been involved in nonacademic activities and are unable to manage the academic home environment. As a result their children were irregular and absent, and they were involved in nonacademic activities, which are more favourable for the poverty zone except for extracurricular activities. By addressing students’ diversity and local context, students living in poverty may have done better class participation.